Perancangan Sistem Informasi Total Productive Maintenance (TPM) Produksi Kertas Berbasis Web pada PT. Indah Kiat Pulp & Paper Serang - Tarigan, Rehulina; Korneilis, Korneilis; Usman, Andi Usri (Teknik Informatika Fakultas Ilmu Komputer, 2025)
TPM system at PT. IKPP Serang is still running by entering machine damage data by filling in the TPM form by the production team and submitting it to the TPM staff. Reporting like this takes a long time (1-2 days) because there is double input (form filling and MS Excel). Apart from that, monitoring and control between production leaders and technicians have not gone well because damage forms often reach the technicians too late. This is less effective and efficient because it will slow down the time it takes for technicians to find out about machine damage. Delays in execution impact the production process and disrupt product quality. Designing a web-based TPM information system is needed to overcome this problem. The system development method uses waterfall with UML (Unified Modeling Language) modeling. This system iincrease the smoothness of the production process and machine repairs can be monitored and controlled .